Evolution of Medical Geography: An Overview - Nepal, Pashupati (Geographical Journal of Nepal, 2009)
Health is not merely absence of disease or informity, it is a state of complete physical, mental and social well-being. Infact, health is dynamic equilibrium between man and his environment. A commission on medical geography was made by international Geographical Union (IGU) and its report was discussed at IGU congress in Washington in 1952. Since then the analysis of health and disease through man-environment relationships has attracted the attention of geographers to work in medical geography. In this context, present article seeks to analyse the development, purpose and field of medical geography. It also attempts to analyse environmental control of disease and susceptibility and prospects of medical geography in Nepal. Finally, it concludes that geographers can make major contributions to help reduce suffering of human health and increasing longevity if they are able to establish causal links between specific disease and environment. The Geographical Journal of Nepal, Vol. 7, 2009: 33-40